THE CHUYA EARTHQUAKE AND ITS AFTERSHOCKS - Gol'din S.V.; Seleznev V.S.; Emanov A.F.; Filina A.G.; Emanov A.A.; Novikov I.S.; Vysotskii E.M.; Fateev A.V.; Kolesnikov Yu.I.; Podkorytova V.G.; Leskova E.V.; Yarygina M.A. (My University, 2004)
On September 27, 2003 (11:33 GMT), an earthquake with a Richter-scale magnitude of M = 7.5 occurred in the Chuya River valley (epicenter 50.04° N, 88.07° E) in the mountainous range between the Chuya and Kuraya depressions in Gornyi Altai. This is the strongest earthquake that has been recorded over the instrumental period of seismological observations in the Altai-Sayan folded region. The epicenter of the Chuya earthquake is located in the center of the local network of ten digital seismic stations (Altai seismological test area) established in August 2002. In summer 2003, this test area was supplemented with two more stations. During these years, networks of temporary stations were twice installed in the future earthquake source zone. After the main shock, a network of temporary stations was again installed in the epicenter zone. This article presents the results of a seismic study in the Chuya-Kuraya zone before and after the Chuya earthquake and reconstructs the scenario of this seismic activity.